Employee Health Management as Part of Corporate Culture and Productivity Tool - A. I. Sosnilo; D. A. Snetkova (Управленческое консультирование)
The article analyzes modern methods of personnel health management and provides examples of the implementation of the most interesting methods in foreign and Russian companies. The rationale is presented that the launching of healthcare management system can contribute to the improvement of competitiveness and growth of employee productivity, strengthening of corporate spirit, as well as creates a positive image and reputation of the company. The authors analyze the dynamics of the VHI market as one of the most demanded practices on care for the health of employees in Russia. The calculations are made on the dynamics of concluding VHI contracts with individuals and legal entities. The authors determine the dynamics of the average premium on VHI with legal entities for the last three years and the rates of increase of the volume of contracts from 2015 to 2019. Also the rolling factor of insurance payments is calculated. The forecast of the volume of VHI contracts with individuals for 2020–2022 is made. Also examples of the application of international medical voluntary insurance policies (MMS) in the performance of offi duties in dangerous working conditions, which can lead to the emergence of professional or serious diseases, are provided. The data on medical start-ups, which are able to positively aff the care of companies about the health of employees, are summarized. The authors provide data on practices on employee health care in domestic companies Lukoil, Rostelecom, Sberbank, Seventh Continent, etc., as well as data on cost savings of companies in the implementation of the system of employee health management. Some recommendations on the application of methods of managing the health of employees in domestic companies are presented.